Pengaruh Faktor-Faktor Produksi Padi Sawah di Lahan Bekas Tambang di Kabupaten Merangin - Gina Fauzia; Elwamendri Elwamendri; Aulia Farida (Seminar Nasional Lahan Suboptimal, 2020)
Fauzia G,  Elwamendri E, Farida A.  2020.  The influence of production factors of sawah rice in mining used land in Merangin district. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The role of the agricultural sector in Jambi Province is still very important and proportionally tends to increase from 2012-2016 with an average increase of 11,28%. Desa Baru Pangakalan Jambu Merangin Regency is one of the areas that has good potential in the agricultural sector, especially lowland rice crops which can contribute to Jambi Province. Land exploitation activities by carrying out illegal mining have resulted in areas in parts of Merangin Regency changing functions. This has had a major impact on lowland rice production. In an effort to restore agricultural land, farmers are faced with quite complex problems, both from within and outside the farm. The aim of this study 1)describe the description and activities of rice farming in the former crate land and 2) determine the effect of production variables on lowland rice farming productivity. The research method was carried out purposively with descriptive and quantitative analysis. The results showed that for the purpose of 1) it was concluded that lowland rice farming activities in the reclaimed land were not different from other lowland rice farming, it only took a long time to restore the land conditions 2) the results of the estimation of the paddly field rice productivity fuction equation state that production variables that have segnificant effect are seed, urea, SP36, Curacon and gramxone, which are shown to have a probability value smaller than the 0,05 level of 0,000; 0,047; 0,043; 0,030 and 0,028. And the variables that do not have a significant effect are KCL Organik, Decis , and labor. With a probaility value greater than the real level of 0,918; 0,864; 0,532; and 0,384. The challenge faces by farmers is controlling the risk of lowland rice farming in former gold mining areas, especially in terms of price.